Equivalent quasi-norms involving differences and moduli of continuity in anisotropic Nikol’skii-Besov spaces - Halim, Benali; Senouci, Abdelkader (Eurasian Mathematical Journal, 2016)
In this paper we study the equivalence of quasi-norms in the anisotropic Nikol’skii-Besov \( B^l_p,θ(R^n) \) spaces involving differences and moduli of continuity for \( 0 < p, θ ≤ ∞ \).